Dipolar DC Induced Collisional Activation of Non-Dissociated Electron-Transfer Products - Adhikari, Sarju (J Mass Spectrom, 2019)
The application of electron transfer and dipolar direct current induced collisional activation (ET-DDC) for enhanced sequence coverage of peptide/protein cations is described. A DDC potential is applied across one pair of opposing rods in the high-pressure collision cell of a hybrid quadrupole/time-of-flight tandem mass spectrometer (QqTOF) to induce collisional activation, in conjunction with electron transfer reactions. As a broadband technique, DDC can be employed for the simultaneous collisional activation of all the first-generation charge reduced precursor ions (e.g., electron transfer no-dissociation or ETnoD products) from electron transfer reactions over a relatively broad mass-to-charge range. A systematic study of ET-DDC induced collision activation on peptide/protein cations revealed an increase in the variety (and abundances) of sequence informative fragment ions, mainly c- and z-type fragment ions, relative to products derived directly via electron transfer dissociation (ETD). Compared to ETD which has low dissociation efficiency for low-charge-state precursor ions, ET-DDC also showed marked improvement, providing a sequence coverage of 80–85% for all the charge states of ubiquitin. Overall, this method provides a simple means for the broadband collisional activation of ETnoD ions in the same collision cell in which they are generated for improved structural characterization of polypeptide and protein cations subjected to ETD.